Penerapan Model Pembelajaran Concept Sentence (Cs) Untuk Meningkatkan Keterampilan Menulis Karya Fiksi Pada Siswa Kelas VIII SMP N 21 Kota Bengkulu - Natiara Oktavi; Adisel; Welti Wediasti (JURNAL ARMADA PENDIDIKAN, 2025)
Application of the Concept Sentence (CS) Learning Model to Improve Fiction Writing Skills Among Grade VIII Students at SMP N 21 in Bengkulu City. This study aims to: to describe how the CS learning model can improve students' fiction writing skills. In Grade VIII students at SMP N 21 in Bengkulu City. This study is a classroom action research project. The research subjects are one Indonesian language teacher and 34 students. The objective is to improve students' ability to write fiction. The data collection techniques used in this study were observation, interviews, and documentation. The data analysis technique was qualitative descriptive analysis with percentages. The results indicate that students' fiction writing skills improved after instructional improvements were implemented through the Concept Sentence (CS) learning model. The improvement in writing skills can be demonstrated by the fact that their scores were above the previously established KKTP. The previous standard was 75. Therefore, it can be concluded that the Concept Sentence (CS) learning model improves students' fiction writing skills in eighth grade D.